1986
DOI: 10.1203/00006450-198605000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Chemotaxis and Neutrophil (Polymorphonuclear Leukocyte) Function in Glycogenosis Type IB

Abstract: ABSTRACT. Polymorphonuclear leukocyte (PMN) func-GSD type IB is characterized by the clinical features of glucosetion was investigated in two patients with glycogen storage 6-phosphatase deficiency (GSD type IA), including hepatomegdisease type IB and neutropenia. Glycogen storage disease aly, growth retardation, fasting hypoglycemia, and lactic acidosis, type IB was documented by liver biopsy and a normal but normal latent enzymatic activity in the liver (l,2). Biochemamount of latent glucose-6-phosphatase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 23 publications
6
15
0
1
Order By: Relevance
“…The study population consisted of three unrelated GSD lb patients: two females aged 3 and 8 yr and one male aged 22 yr; two ofthese patients have been previously reported (14). Also enrolled in the study were seven unrelated GSD la patientsbetween the ages of 5 and 28 yr of which four were males and three were females.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study population consisted of three unrelated GSD lb patients: two females aged 3 and 8 yr and one male aged 22 yr; two ofthese patients have been previously reported (14). Also enrolled in the study were seven unrelated GSD la patientsbetween the ages of 5 and 28 yr of which four were males and three were females.…”
Section: Methodsmentioning
confidence: 99%
“…There is in-HMPS, hexose monophosphate shunt; la and lb, types la and lb of GSD. creasing evidence of functional defect(s) in GSD lb patients' phagocytic cells which limits their ability to destroy invading microorganisms. Defects in neutrophil chemotaxis and bactericidal activity have been described (8,(12)(13)(14)(15)). An important mechanism in phagocyte bactericidal activity is a process termed respiratory burst activity.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple functional abnormalities have been identified including chemotaxis, bactericidal activity, respiratory burst activity, and glucose transport (12)(13)(14)(15)(16)(17)(18). We previously demonstrated that the defect in respiratory burst activity was associated with impaired calcium mobilization and decreased intracellular calcium stores (18,19).…”
Section: ---mentioning
confidence: 99%
“…As alteraçÔes dos neutrĂłfilos incluem mobilidade e aderĂȘncia reduzidas, defeitos na atividade bactericida e fagocitose, redução na produção de Ăąnion superĂłxido e da atividade do shunt da hexose-monofosfato (HMP) 39 . Apesar dos diversos trabalhos demonstrarem essas alteraçÔes, a patogĂȘnese permanece desconhecida 36 .…”
Section: Glicogenose Ibunclassified